Co-benefits for cropland yield, nitrogen emissions, and climate impact through multi-objective optimization agricultural manure solutions - Yinghua Yin; Shufang Guo; Qiyu Xu; Jian Liu; Hongyuan Wang; Yanhua Zhuang; Zhen Wang; Lingling Hua; Hongbin Liu; Limei Zhai (Nature Communications)
Abstract Optimizing manure use and reducing chemical fertilizers are crucial for achieving the Sustainable Development Goals. However, optimal manure redistribution for cropland yield, nitrogen emissions, and greenhouse gas benefit remains unclear at large spatial scales. Here, we employed genetic algorithms and meta-analysis to obtain an optimal substitution rate for major crops in China. This could reduce synthetic nitrogen use and reactive nitrogen pollution by 13.3 and 2.0 Tg, cut ammonia and nitrous oxide emissions by 15.6% and 16.2%, and lower nitrogen runoff and leaching by 32.9%. The yield of eight major upland crops could be increased by 2.0-19.5%. The strategy involves relocating about 255 million pig equivalents, with 32.3% moved across provinces, mainly from central to northern and northeastern China. An estimated US$6.1 billion investment in livestock relocation could yield US$25.9 billion in benefits.